Characterization of stimulus response curves obtained with transcranial magnetic stimulation from bilateral tibialis anterior muscles post stroke. (20th November 2019) - Iyer, Pooja C.; Madhavan, Sangeetha
Highlights: To determine the type of analyses for TMS-generated stimulus response curves. Non-linear fit explained greater variability than linear analyses. Area under the curve measure was not different between both approaches. Abstract: Background: Stimulus response curves (SR curves), measured using transcranial magnetic stimulation (TMS) induced motor evoked potentials (MEP), yield important information regarding corticomotor connectivity. Limited understanding of SR curve analyses techniques for leg muscles after stroke may limit the utility of TMS data for walking recovery. Objective: To compare linear and non-linear curve fitting for MEP responses from the non-paretic and paretic tibialis anterior (TA) muscles. Methods: Accuracy of fit was measured using coefficient of determination (R 2 ). Similarities of the fit were compared using slopes and area under the curve (AUC). Results: The non-linear function demonstrated higher R 2 and slopes. The AUC was not significantly different between the two analyses approaches. The non-linear non-paretic SR slopes and paretic AUC had significant associations with walking speed. Conclusion: Our results highlight the differences between non-linear and linear approaches to best fit the SR curves from bilateral TA muscles in stroke survivors. Although the linear function can appropriately fit the SR curve of the paretic and non-paretic TA, the non-linear function estimated a higher slope. We found the AUC to be a more robust measure that was not affected by the type of curve-fitting approach and only the AUC of the paretic TA showed significant association with walking speeds. A better understanding of SR curve fitting approaches for the TA muscles in individuals with chronic stroke allows for their optimal use in interpretation of TMS data and literature.